The Substitution Effect of Fetal Bovine Serum to Platelet-Rich Plasma on Stem Cell Proliferation - Rosadi, Imam; Karina; Afini, Irsyah; Widyastuti, Tias; Sobariah, Siti (Biosel Biology Science and Education, 2024)
Stem cells are capable of self-regeneration and differentiation into specialized cells, such as adipocytes, chondrocytes, and osteocytes. Stem cells can be cultured in vitro using media-containing serum, such as fetal bovine serum (FBS). However, the cell yield is often lacking, thus the manipulation of the culture medium is needed. Platelet-rich plasma (PRP) contains a thousand growth proteins. This study aims to compare the effects of FBS (Gibco), non-commercial PRP, and commercial PLTGold® Human Platelet Lysate (Merck) on the growth and population doubling time (PDT) of stem cells isolated from adipose tissue. Stem cells will be enzymatically isolated from adipose tissue, followed by culture and expansion processes, with subsequent observations of cell morphology, viability, growth rate, and PDT. The results showed that adipose-derived stem cells exhibit fibroblast-like morphology and adhere to the plastic surface. The optimal cell number, PDT and proliferation rate showed in PLTGold®, PRP and FBS respectively. Based on these results, it can be concluded that PLTGold® or PRP can substitute FBS as a growth supplement for stem cell proliferation.  Keywords: Stem Cell, Proliferation, PDT, PRP, PLTGold®